Mindfulness, Mental Health and HIV Outcomes Among Female Sex Workers in the Dominican Republic and Tanzania. - Kerrigan, Deanna; Karver, Tahilin Sanchez; Barrington, Clare; Donastorg, Yeycy; Perez, Martha; Gomez, Hoisex; Mbwambo, Jessie; Likindikoki, Samuel; Davis, Wendy; Wilson Beckham, S.; Mantsios, Andrea; Galai, Noya; et al. (AIDS & Behavior, 2021)
We examined the relationship between mindfulness, mental health and HIV outcomes among female sex workers (FSW) from the Dominican Republic (DR) (n = 201) and Tanzania (n = 208) using cross-sectional survey and biologic data. We employed stratified multivariate linear and logistic regression. Depression was associated with lower odds of ART adherence in the DR (AOR 0.25, 95% CI: 0.08–0.78) and of viral suppression in Tanzania (AOR 0.49, 95% CI: 0.24–0.97). In both countries, mindfulness was associated with lower odds of moderate to severe depression (AOR 0.82, 95% CI: 0.76–0.88 for the DR; AOR 0.85, 95% CI: 0.77–0.95 for Tanzania). In the DR, mindfulness was associated with lower odds of anxiety (AOR 0.83, 95% CI: 0.77–0.89), lower HIV stigma (β = − 0.28 per unit change, 95% CI: − 0.37 to − 0.19) and greater odds of viral suppression (AOR 1.09, 95% CI: 1.02–1.15). Findings demonstrate the potential of tailored mindfulness interventions to improve mental health and HIV outcomes among FSW.